The effects of marijuana smoking on peri-implant health parameters. - Naguib, Nader. (Tufts University. Tisch Library., 2023)
Thesis (M.S.)--Tufts University, 2023.; Submitted to the Dept. of Periodontology.; Advisor: Livia Valverde.; Committee: Lorenzo Mordini, Y Natalie Jeong, Sarah Pagni, Arthur Schwartz, and Samar Shaikh.; Keyword: Dentistry.